Crosscultural Communication Nias Ethnic and Minangkabau Ethnic in Nagari Sungai Buluah Barat - Putra Yendri Zal; Nunik Hariyanti (LPPM Stikosa - AWS, 2022)
Cross-cultural communication occurs between individuals and groups who have different cultural backgrounds. One case of communication in the perspective of cross-cultural communication is between the Nias community and the Minangkabau community in Nagari Sungai Buluah Barat, Padang Pariaman, West Sumatra. This study aims to describe how cross-cultural communication occurs in the Nias and Minangkabau tribal communities in Nagari Sungai Buluah Barat using the six cultural dimensions proposed by Hofstede. The method used in this research is descriptive qualitative. The number of resource persons in this study amounted to six people. The data collection techniques used in this study were observation, interviews, documentation, and the Face Negotiation Theory theory to analyze the research results. This study indicates that the Nias and Minangkabau tribes in Nagari Sungai Buluah Barat have reached a form of compromise and mutually accept all conditions of differences and then maintain boundaries in acting to create harmony. They have the awareness that they are only the next generation who continue the concept of life passed down by their ancestors long ago. A Malakok tradition is a form of assimilation of Minangkabau culture to Nias because Nias is an immigrant to Minangkabau land.